2021
DOI: 10.1007/s10329-021-00928-4
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-three-year demographic history of the Affenberg Japanese macaques (Macaca fuscata), a translocated semi-free-ranging group in southern Austria

Abstract: Demographic studies on translocated primate groups provide a unique opportunity to study population dynamics, social strategies, and reproductive parameters of a species adapting to new environments. In 1996, 38 Japanese macaques (Macaca fuscata) of the Minoo-H group (Osaka Prefecture, Japan) were translocated to Affenberg Landskron, a four-hectare naturally forested park in southern Austria. By January 2020, the population had increased to 160 individuals, and a total of 223 births were recorded. Births peake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“…Kin favoritism and nepotism are integral properties of Japanese macaques and, in general, despotic societies (11, 37, 38). Our study group followed species-typical matrilineal norms, i.e., the presence of distinct hierarchical ranks and order (25, 39, 40). As hypothesized, kinship was found to influence prosociality, though it did not predict the propensity or likelihood of prosocial provisioning, suggesting a general tendency to help group members.…”
Section: Discussionmentioning
confidence: 99%
“…Kin favoritism and nepotism are integral properties of Japanese macaques and, in general, despotic societies (11, 37, 38). Our study group followed species-typical matrilineal norms, i.e., the presence of distinct hierarchical ranks and order (25, 39, 40). As hypothesized, kinship was found to influence prosociality, though it did not predict the propensity or likelihood of prosocial provisioning, suggesting a general tendency to help group members.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent data on male social rank before fission was collected in 2018 (Schmidhuber, unpublished data). Nevertheless, Pflüger et al (2021) found the male dominance hierarchy in the Affenberg-group to be very stable concerning high-ranking positions, and that it followed a gradual succession of alpha-positions.…”
Section: Validity Control-demographicsmentioning
confidence: 90%
“…The Affenberg‐group originates from a wild group that was translocated from Minoo to Affenberg, Austria in 1996. The demographic development, population dynamics, social characteristics, and reproductive parameters of this group have been extensively documented since their arrival at Affenberg (Pflüger et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations